Evaluation of Sweet Basil Powder Plant (Ocimum basilicum L.) as a Feed Additives, on the Performance of broilerChicks: Thair Jawad Kadhim Al-Kelabi@ and Galib M. Al-Kassie - Kadhim Al-Kelabi, Thair Jawad (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was carried out at the Poultry Farm, College of Veterinary Medicine -Baghdad University, for powder sweet basil plant evaluation as feed additives, and its effect on the performance and health of broiler. Three hundred one day old Hubbard broiler chicks were used in this study. Chicks were weighed and randomly divided into 10 treatments groups, with 2 replicates (15chicks each).These groups were fed with the following rations: The 1st group was fed the basal diet (control group).The 2nd,3rd and 4th groups were fed the basal diet+0.3, 0.4 and 0.5 % basil powder for the first 3 weeks only respectively. At the 5th, 6th and 7th groups were fed the same basal diet +0.3, 0.4 and 0.5 % basil powder for the second 3 weeks respectively. While the 8th, 9th and 10th were fed the same basal diet with 0.3, 0.4 and 0.5 % basil powder along the whole six weeks. The experiment was terminated when birds were 6 weeks old. Weight gain, feed intake and feed conversion ratio were measured at the end of first three weeks and also at the end of the experiment. The results revealed that adding sweet basil powder significantly (P< 0.05) increased live body weight, body weight gain and feed conversion ratio as compared with the control, especially on the level 3%, 4%, 5% of Sweet basil powder addition along the whole period of the experiment and There was a significant (P< 0.05) decrease in total feed intake compared with the control group.